TOWARDS EPISTEMIC JUSTICE: DECONSTRUCTING GLOBAL KNOWLEDGE FROM A SOUTHERN PERSPECTIVE - Badruddin, Syamsiah ; Halim, Paisal; P, Suci Ayu Kurniah (Universitas Nasional, 2025)
This article critically examines the dominance of Western epistemology in global knowledge production and its impact on the marginalization of local knowledge in the Global South. Using the frameworks of decolonizing knowledge and epistemic justice, it investigates how global academic structures perpetuate inequalities in the validation, distribution, and legitimation of knowledge. The research identifies several key challenges to epistemic independence, including intellectual dependency, the marginalization of indigenous knowledge, language barriers, infrastructure limitations, and internal fragmentation. In response, the article proposes decolonial strategies such as curriculum reform, strengthening local research institutions, fostering South–South collaboration, and advocating for policies that recognize diverse epistemologies. The objective is to create a more equitable, inclusive global knowledge ecosystem that reflects the social realities of the Global South.